Export Orientation, Foreign Production, and the Growth of Medium Sized and Large Manufacturing Firms - Michael Pfaffermayr (Austrian Institute of Economic Research (WIFO), 2000)
Using data on large and medium sized Austrian manufacturing firms this paper analyzes empirically in which way a high degree of export orientation and foreign production abroad, as two modes of serving foreign markets, are related to the growth performance of domestic production. Robust median regressions do not suggest that foreign production adversely affects firm growth at the domestic location. Exports to non-EU countries, in combination with foreign production, especially contribute to growth at the domestic location.
Keywords: L11; F23; 330; Growth of firms; multinational firms; exports; Unternehmenswachstum; Multinationales Unternehmen; Export; Österreich